Cytokinin modulates the inhibitory effect of shade stress on photosynthesis, antioxidant capacity and hormone homeostasis to regulate the grain yield in wheat - Yongqiang Zhang; Yongqiang Zhang; Yongqiang Zhang; Juan Li; Juan Li; Qijiang Xu; Qijiang Xu; Chuanxin Chen; Chuanxin Chen; Shihui Nie; Shihui Nie; Junjie Lei; et al. (Frontiers in Plant Science)
Agroforestry intercropping is an effective way to optimize land use and ensure food security. However, the physiological mechanism by which the shading of dominant plants inhibits the yield of non-dominant plants in this mode remains to be investigated. A two-year location experiment of walnut-winter wheat intercrop combined with exogenous 6-benzyladenine (6-BA, the first synthetic cytokinin) treatment was conducted to reveal the mechanism of 6-BA in inhibiting wheat growth and yield formation under shade stress by measuring the photosynthetic characteristics, antioxidant capacity, hormone homeostasis of wheat flag leaves and yield. The results showed that compared with far canopy area (FCA), antioxidant enzyme activity [e.g. superoxide dismutase (SOD), peroxidase (POD)], zeatin (ZT) and abscisic acid (ABA) content and photosynthesis of wheat flag leaves were significantly reduced in below canopy area (BCA) treatment during flowering and grain filling stages, thereby inhibiting wheat dry matter accumulation and yield formation. Exogenous 6-BA significantly increased hormone [i.e. indoleacetic acid (IAA), ZT and gibberellin (GA)] levels, antioxidant enzyme activities and photosynthesis in flag leaves, thereby increasing dry matter and yield, especially in the FCA condition. Furthermore, net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci), activities of ribulose bisphosphate carboxylase (RuBPCase) and phosphoenolpyruvate carboxylase (PEPCase), ABA and ZT concentrations of flag leaves at flowering and filling stages had a significant contribution to yield formation under 6-BA and shade treatments. Overall, cytokinin regulates the inhibitory effects of shade stress on wheat photosynthesis, antioxidant capacity and hormone homeostasis to reduce wheat yield loss.